Design and control of automotive propulsion systems - Sun, Zongxuan; Zhu, Guoming (Engineer) (CRC Press, 2015)
"This book presents analytical and experimental methods and achievements in designing mechanical and mechatronic driveline systems. Examples include various power dividing units, including symmetric and non-symmetric varieties, as well as open and lockable differentials, various limited slip differentials, no spins, and viscous clutches. The text presents logic control algorithms used to control vehicle power dividing units and designs of torque/power managing devices. The authors' approach to designing driveline systems is that characteristics and parameters of a driveline system and a set of power dividing units are established through vehicle performance and energy-fuel efficiency analysis and optimization"-- Provided by publisher
Keywords: Automobiles -- Motors -- Design and construction.; Automobiles -- Power trains -- Design and construction.; Propulsion systems -- Automatic control.; elektronické knihy; electronic books